The Role of the Private and the Public Sector in Health Care - Orosz, Éva (Szociológiai Szemle, 2024)
This paper concentrates on only one question from among the wide range of themes concerning the roles and relations of the private and public sector, namely the probable economic and social effects of a possible fundamental change in the structure of funding of the Hungarian health system resulting from a radically increasing share of the private sector. By way of introduction it is necessary to briefly mention two issues. One is the radically different developmental tendencies between the health care systems in Western Europe and in the USA. The other, related matter concerns the main features of the health market.